Tissue Doppler–Derived Contractile Reserve Is a Simple and Strong Predictor of Cardiopulmonary Exercise Performance across a Range of Cardiac Diseases. Issue 5 (15th January 2013) - McIntosh, Robert A.; Silberbauer, John; Veasey, Rick A.; Raju, Prashanth; Baumann, Oliver; Kelly, Sarah; Beale, Louisa; Brickley, Gary; Sulke, Neil; Lloyd, Guy W.
<x xml:space="preserve">Abstract</x> Background Resting echocardiographic measures of cardiac function such as left ventricular ejection fraction correlate poorly with exercise capacity. Assessment during exercise using measures less dependent on hemodynamic loading conditions, such as tissue Doppler imaging (TDI), may more accurately characterize the relationship between cardiac function and exercise capacity. Methods and Results One hundred one subjects with various cardiac diagnoses underwent exercise stress echocardiography with simultaneous cardiopulmonary gas exchange analysis. Standard two‐dimensional, Doppler and spectral TDI parameters were assessed at both rest and peak exercise. Across all subjects the strongest relationship with peak oxygen uptake (pVO2) was with peak left ventricular systolic tissue velocity (S′) during exercise (r = 0.84, P < 0.001). The strength of the relationship was greater than that observed with any other common echocardiographic measure of systolic or diastolic cardiac function. Conclusion There is a very strong relationship between measurements of S′ during exercise and exercise capacity. The previously observed poor correlation with standard measures of systolic and diastolic cardiac function may be explained both by the load dependence of parameters such as ejection fraction and by reliance on resting as opposed to exercise assessment.